The origin and impact of an ESL teacher's beliefs on curriculum design. Issue 3 (3rd July 2021) - Shieh, Jin-Jy; Reynolds, Barry Lee
ABSTRACT: Teachers in institutions of higher education have a very high degree of freedom when designing curricula. They make decisions on learning objectives, content, content organization, teaching arrangement, and assessment. Teachers' beliefs regarding curriculum design affect decision-making and planning processes, teaching approaches, and their relationships with students. This study aimed to examine the role beliefs played in influencing an English as a Second Language (ESL) teacher's curriculum design. The teacher's beliefs, their origins, and their impact on curriculum design were investigated through the analysis of in-depth interview transcripts, course outlines, teaching and learning materials, and teaching reflection notes. The results of the analysis revealed that the ESL teacher believed that an ESL curriculum should be balanced, authentic, and enjoyable. While teaching experiences, article reading, and personal interests were shown to have shaped the ESL teacher's beliefs, the most significant influencer was his personal experiences in a postgraduate Teaching English to Speakers of Other Languages teacher education programme. This finding underscores that quality curricula will bring about positive learning experiences, which, in turn, will lead to better curriculum design.